A Bibliometric Analysis of Impulsive Buying Research in Business and Management: Trends, Collaboration, and Future Research Directions (2020–2026) - Yunita Kartika Sari; Bambang Widjanarko (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Impulsive buying is the most topic in consumer behaviour and marketing study due to digital commerce, social media, and mobile technologies development. Unfortunately, a comprehensive overview of collaboration patterns, intellectual structure, and emerging research themes are still limited. This study aims to map the development of impulsive buying research within the Business, Management and Accounting discipline using a bibliometric approach. The data is retrieved from the Scopus database using query TITLE-ABS-KEY("impulsive buying") with additional filters restricting documents to journal articles, English language, final publication stage, and the Business subject area published between 2020 and 2026. This study employs VOSviewer to analyse 250 articles that meet selection criteria examining keyword co-authorship, co-occurrence, countries, and organizations, overlay, network, and density visualizations. The publications increase after 2022 reflecting increasing academic interest in impulsive buying. Research themes evolve from traditional consumer behaviour toward livestream shopping, Generation Z, social commerce, trust, materialism, scarcity, and technology-enabled purchasing behaviour. Collaboration analysis indicates China, Indonesia, India, Malaysia, and the United Kingdom as the most influential contributors. These findings provide a comprehensive understanding of impulsive buying research current intellectual landscape and identify promising directions for future studies.